STUDY OF MINERALS THAT CONTROLLED CALCIUM,MAGNESIUM AND IRON SOLUBILITY AND THEIR RELATION SHIPS WITH SOIL CONSERVATION USING SOLUBILITY DIAGRAMS - M. Nafawaah, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Three different calcareous rocks consist mainly of calcite C, dolomite D and its combination C,D were chosen. Rocks Samples Were treated with different concentration of salt Soluations, included CaCl2 (0.2,0.05 molar) (applied to dolomite samples), MgCl2 (applied to calcite samples), and combination of these two salts which applied for both (D-Dolomite and C-Calcite). Other samples from carbonate minerals were treated and incubated with FeSO4.7H2O and Fe-EDDHA at 20Mg-1 mineral. These treated samples subjected to sequence of wetting and drying for 120 days under saturated CO2 atmosphere. At the end of incubation period these samples were air dried and used to conduct the following examinations by using solubility diagrams .Application of solubility diagrams of indicated that the solubility of CaCO3 minerals were controlled by calcite – dolomite and Ikite minerals. Whereas, the diagrams which consider the activity of Mg2+ against pH show that the solubility– precipitation reaction of magnesium carbonate minerals where controlled by calcite– dolomite and Ikite minerals. On other side Sidrate FeCO3 Minerals controlled solubility of different source of  iron (FeSO4.7H2O + Fe-EDDHA) in cubated with carbonate minerals.